BUDAYA ORGANISASI MASYARAKAT DI DESA KANONANG TIGA KECAMATAN KAWANGKOAN KEBUPATEN MINAHASA - LUMENTA, KEZIA VIONA VALENSCA; POSUMAH, JOHNNY HANNY; MAMBO, RULLY (Sam Ratulangi University, 2020)
The organizational culture in Kanonang Tiga Village is called Kerukunan or Pillars. In which themembers are families in Kanonang Tiga Village or outside the village, each member is obliged to pay thesettlement fees set by the respective pillars, which later the collected funds will be given to the families ofthe members of the pillars that occur. The method used is descriptive with a qualitative approach. Theinformants in this study include the Head of Kanonang Tiga Village, Secretary of Kanonang Tiga Village,Management and Members of the Family Pillars, Management and Members of the Three Pillars ofKanonang Village, Managers and Members of the Neighborhood Association. Data collection techniquesused by data collection, data reduction, data presentation, and drawing conclusions. The results of thestudy show that the application of the Involment dimension in the deliberation has been going well andmust always express a common interest and also accept every opinion. Consistency in unity and unitybecomes very important because without the existence of unity and unity then what was previously thegoal and target will not be maximally achieved. adaptability is a way to maintain togetherness in thisorganization between management and members who are still awake and up to now maintained. MissionDimension The implementation of goals and missions in the organization has been running well, onlythere are only a few parties who have not optimally carried out their responsibilities. The advice given inthis research is if it continues to maintain things that are already good in this community organization inorder to achieve organizational goals.Keywords: Organizational Culture, Society.